Apakah Attractiveness of Rucas Endorser Berpengaruh terhadap Attitude dan Purchase Intention? - Syarifah Siti Wartini; Giriati; Erna Listiana; Barkah; Ana Fitriana (Forum Kerjasama Pendidikan Tinggi, 2025)
Marketing strategies can be designed to reach a wider audience by utilizing various communication platforms, such as online promotions and content marketing. The unique content approach used by Rucas, namely highlighting unconventional advertising models, has succeeded in getting a positive response from users of social media platforms. This study analyzes how the success of the Rucas brand is influenced by the appeal of supporters perceived by social media users, which can then influence Purchase Intention with Attitudes toward advertising and the brand as mediating variables. This study involved a population of all individuals who knew about Rucas brand advertisements on social media, with a sample size of 225 respondents selected through purposive sampling. Data collection was conducted by distributing questionnaires via social media platforms. The hypothesis in this study will be tested using a causal approach and Structural Equation Modeling (SEM).The results showed that the appeal of supporters had a significant effect on Attitudes towards advertising and brands, which influenced Purchase Intention. However, supporters' appeal did not positively Impact Purchase Intention unless mediated by the Attitude variable. This study provides important implications for marketing strategies, especially in choosing the right Endorser to increase Purchase Intention